The Determinants of Islamic Banks’ Non-Performing Financing in the Small-Medium Enterprises (SMEs) Sector - Fakhrunnas, Faaza; El Hasanah, Lak Lak Nazhat (Universitas Muhammadiyah Yogyakarta, 2022)
The performance of Islamic banks in financing activities is determined by many factors, including macroeconomic variables and internal factors, such as the financial performance of the bank. The study investigates the determinant of non-performing financing (NPF) of Islamic banks in Indonesia, particularly in Small-Medium Enterprises (SMEs) sector. Adopting the panel data analysis, the data comprise 33 provinces in Indonesia starting from 2016m1 to 2021m07, equal to a 2211 observation period. The study reveals that the size of the bank’s asset and financing to deposit ratio (FDR) of Islamic banks has a significant relationship to NPF value in SMEs sector, and the impact remains unchanged in the period before and during the COVID-19 pandemic. From the regional viewpoint, the size of the bank’s assets also has a significant influence on NPF in the provinces located in Java but not outside of Java. As a policy implication, the study suggests that the size of a bank’s assets must be enhanced with prudent risk management in financing activities in the SME sector. Surely, the policy can be implemented in a top-down approach through government and financial authority; then it also can be applied bottom-up approach through the bank’s business activities. Finally, as the limitation of the research, the study only utilizes limited variables and uses a single-country analysis which can be improved and extended for future study.